Synthesis of 4, 8-dimethoxy-1-naphthol via an acetyl migration. Issue 6 (19th March 2017) - Zhang, Qijing; Dong, Jinyun; Cui, Qing; Li, Shaoshun; Cui, Jiahua
ABSTRACT: Based on acetyl migration, an efficient synthesis of 4, 8-dimethoxy-1-naphthol(1) has been achieved with high overall yield. Compared with the reported method, there were several advantages. First, the reaction conditions were mild. Second, the workup of each step was much simpler. Third, juglone as the starting material in the synthesis was readily available. The solvent and reaction temperature greatly influenced the migration process. GRAPHICAL ABSTRACT: